Smallholder farmers' perception on climate change, information needs and adaptation strategies for improved pineapple (Ananas comosus) production in Awaé Cameroon - Mekam Chantal Tchoupe; Ekwa Yawa Monono; Estelle Assonwa; Kame Hannah Liengu Monono; Elisabeth Sailieh Mbomi (Open Journal of Environmental Biology - Peertechz Publications, 2023)
This study examined smallholder pineapple farmers' experiences of climate variability and change in production, as well as ranked adaptation and information source options using data from primary sources. The primary data consisted of a survey on pineapple growing in Awaé. The analysis revealed that pineapple farmers experience climate variability and change evidenced mainly through irregular rainfall patterns (100%), excessive heat (97.14%), drying of streams (85.71%), and rising temperatures (77.14%). These variabilities cause a change in color and taste (40.00 and 45.71% respectively), a reduction in fruit size and yield (68.57 and 100% respectively), and consequently, a reduction in income from pineapple production. Farmers identify deforestation (54.29 ± 0.51%), bush fires (34.29 ± 0.48%) as the major causes of climate change. Although the use of soil conservation practices (e.g. mixed and rotational cropping), bush fallow and crop diversification emerged as the three main adaptation options employed by smallholder pineapple farmers, climate change has the potential to reduce pineapple production in Awaé. Therefore there is a need for future studies to identify adaptation measures that will help improve pineapple production in the area. These farmers are willing to receive information commencement of rain, the prediction of stopping rain, the impact, adaptation strategies, and mitigation strategies to climate change. They can be informed through phone text messages, television, radio, and even demonstration methods for them to effectively follow up on climate change to better improve their pineapple production in Awaé.